Performance evaluation of two grid-connected solar photovoltaic systems under temperate climatic conditions in South Korea. (November 2022) - Owolabi, Abdulhameed Babatunde; Yakub, Abdulfatai Olatunji; Li, Hong Xian; Suh, Dongjun
Abstract: This study evaluates two grid-connected solar photovoltaic (PV) systems using five criteria: final energy output, system yield, performance ratio, capacity factor, and system efficiency. The PV systems were installed on the rooftop of the Engineering building, Kyungpook National University, the Republic of Korea. The system was monitored, and necessary environmental data was recorded from January 2021 to December 2021. From the result, the annual electricity exported to the grid by the m-si solar PV was 9521 kWh, and that of the p-si was 8263 kWh. The m-si has a better annual average daily final and array yield of 5.23 h/day and 5.45 h/day than the annual final and array yield of p-si with 4.93 h/day and 5.12 h/day, respectively The composite solar PV saved the environment from 9.7 tons of CO 2 per year, equivalent to 9.7% of people reducing energy use by 20%. Based on the analysis for this location, the m-si solar cell technology showed a better annual performance than the p-si solar cell when considering the five evaluations, except for the performance ratio where the p-si solar cell outperformed the m-si solar technology. Finally, this study provides insightful information to researchers, PV installers, and PV manufacturing companies on the actual performance of grid-connected solar PV in Korea. Highlights: The performance evaluation of grid-connected solar PV is presented. The annual specific energy yield for m-si and p-si was 1904.2 kWh and 1796.3 kWh. The annual average daily final yield for m-si and p-si was 5.23 h/day and 4.93 h/day. The capacity factor of m-si operates at a higher capacity than p-si by 5.7%. The composite solar PV technology saved the environment from 9.7 tons of CO2 per year.